Exercise improves the social and behavioral skills of children and adolescent with autism spectrum disorders - Toscano, Chrystiane V. A.; Ferreira, José P.; Quinaud, Ricardo T.; Silva, Keity M. N.; Carvalho, Humberto M.; Gaspar, Joana M. (Frontiers in Psychiatry, 2022)
Background Currently, there is no standard treatment for Autism Spectrum Disorders (ASD), but there are many ways to minimize the symptoms and maximize abilities. Some studies suggest that exercise and other physical activities with children with ASD may be beneficial. In this study, we hypothesized that a physical exercise program (48-week exercise-intervention) could improve symptomatology dyad among children and adolescents with ASD. Our main aim was to examine the effects of physical activity on the primary clinical symptoms and associated comorbidities in children and adolescents with ASD. Methods We allocated 229 children with ASD, ranging in age from 2.3–17.3 years (M = 7.8, SD = 3.2), into three groups: (a) exercise- intervention group, (b) control group from the same institution, and (c) control group from another institution. The exercise program was performed at moderate intensity in a 30 min section twice a week for 48 weeks. We used Bayesian multilevel regression modeling to examine participant outcomes and responses to the exercise-intervention. Results Our results showed that a 48-week exercise-intervention substantially decreased ASD social interaction problems, attention deficit, emotional reactivity, stereotypical verbal and motor behavior, and sleep disturbances. However, physical exercise did not affect eye contact and food selectivity. We also observed that ASD severity and socioeconomic status influence eye contact, attention deficit, and sleep disturbance responses. Conclusion In conclusion, children and adolescents with ASD exposed to a 48-week physical exercise-intervention program had important improvements in ASD symptoms. This study highlights that structured exercise programs can be a powerful complementary therapy for the ASD population.